2016
DOI: 10.1089/jpm.2015.0313
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Advance Care Planning Internal Medicine Resident Curriculum: Valuing Our Patients’ Wishes

Abstract: A multimodality curriculum including self-directed learning, lectures, and practice with simulated and actual outpatients with active reflection and feedback is effective in improving resident comfort level and formal training in ACP. Further research is needed to understand whether these interventions will translate into an increased frequency of discussions with patients about ACP after residency training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Participants suggested that provider training could help clarify when and how to initiate ACP conversations. ACP training increases providers’ knowledge, confidence and engagement with patients . Other recommended interventions such as integrating ACP delivery and documentation into healthcare protocols hold great promise because such interventions in the community have increased patient engagement in ACP .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants suggested that provider training could help clarify when and how to initiate ACP conversations. ACP training increases providers’ knowledge, confidence and engagement with patients . Other recommended interventions such as integrating ACP delivery and documentation into healthcare protocols hold great promise because such interventions in the community have increased patient engagement in ACP .…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Other recommended interventions such as integrating ACP delivery and documentation into healthcare protocols hold great promise because such interventions in the community have increased patient engagement in ACP. 27,28 Participants recommended addressing lack of psychosocial support by integrating family into ACP discussions when possible and providing a patient advocate or peer support. A previous study noted that effective ACP was contingent on psychosocial support 22 but further research is needed to understand inmates' unique psychosocial needs during ACP.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies showed improvements in knowledge and self-assessed skills after didactic content, and they both combined traditional didactics with online simulation or role playing. 13,14 Multiple studies explored the benefits of mandated rotations in concert with didactic content, [15][16][17] and all found high learner satisfaction and improved knowledge on posttesting, but no changes in attitudes or behaviors. Numerous curricular interventions focusing on chronic pain and substance abuse were published in the last several years.…”
Section: Curriculum Developmentmentioning
confidence: 99%
“…40 Trainee knowledge, including knowledge of communication strategies, improved. Similar simulationbased ethics and communications curricula have been piloted for neurosurgical residents, 41 internal medicine residents, 42 geriatrics medicine fellows, 43 ethics committee members, 44 nursing students, 45 and nurse-midwifery students. 46 Another innovative pedagogical technique that merges active and passive modalities is the inverted or flipped classroom.…”
Section: New Modalities In Medical Ethics Educationmentioning
confidence: 99%